2018
DOI: 10.3389/fneur.2018.00482
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profiles and Hub Vulnerability in Parkinson's Disease

Abstract: The clinicopathological correlations between aspects of cognition, disease severity and imaging in Parkinson's Disease (PD) have been unclear. We studied cognitive profiles, demographics, and functional connectivity patterns derived from resting-state fMRI data (rsFC) in 31 PD subjects from the Parkinson's Progression Markers Initiative (PPMI) database. We also examined rsFC from 19 healthy subjects (HS) from the Pacific Parkinson's Research Centre. Graph theoretical measures were used to summarize the rsFC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 61 publications
5
37
2
2
Order By: Relevance
“…Untangling the effect of the neuro-degeneration of PD from the effects of regular aging is important for further understanding the functional connectivity in PD patients associated with cognitive deficits. A recent study support this, showing a strong effect of aging on PD patients' cognition (8).…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Untangling the effect of the neuro-degeneration of PD from the effects of regular aging is important for further understanding the functional connectivity in PD patients associated with cognitive deficits. A recent study support this, showing a strong effect of aging on PD patients' cognition (8).…”
Section: Introductionmentioning
confidence: 65%
“…A significant difference in age occurred between the PD-non-MCI and PD-MCI (Table 2). Matching for age of PD-non MCI and PD-MCI, however, might induce a recruitment bias, as many studies indicate that PD patients with MCI are generally older than PD-non MCI (2, 7, 8). Here, we opted for another strategy to investigate the effect of age, we added a young healthy group allowing us to investigate of age vs. the effect of disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that sparse methods are also often used in classification tasks, where they have been observed to provide better prediction but less stable weights (55,56), which indicates a trade-off between prediction and inference (55). Correspondingly, it has been suggested to consider weight stability as a criterion in sparsity parameter selection (55,57,58).…”
Section: Brain-behavior Associationsmentioning
confidence: 99%
“…Different studies showed that male PD patients have worse general cognitive abilities and male sex is the primary predictive factor for mild cognitive impairment and its more rapid progression in the severe stage of the disease [26][27][28]. Accordingly, female PD patients perform better at the Symbol Digit Modalities Test, verbal fluency tests and overall cognition measured by the Montreal Cognitive Assessment scale, but present with worse visuospatial function [29]. Significant sex differences are also observed for frontal executive abilities (attention and working memory), with male PD patients showing greater deficits than female non-demented patients.…”
Section: Non-motor Symptomsmentioning
confidence: 99%